THE KNOWLEDGE LEVEL OF DOCTORS AND INPATIENTS REGARDING PATIENT’ RIGHTS AND OBLIGATIONS IN DENPASAR CITY - Yusran, Queen Fathiha; Rustyadi, Dudut; Henky, Henky; Alit, Ida Bagus Putu (E-Jurnal Medika Udayana; Vol 14 No 6 (2025): E-Jurnal Medika UdayanaDO - 10.24843/MU.2025.V14.i6.P03, 2025)
The relationship between doctors and patients in healthcare services was contractual, creating rights and obligations for both parties. A good understanding of patients' rights and obligations enhanced the quality of healthcare services, fostered a more harmonious doctor-patient relationship, and facilitated better medical decision-making. Therefore, it was essential to assess the level of knowledge among doctors and inpatients regarding patients' rights and obligations in Denpasar City. This study aimed to determine the level of knowledge of doctors and inpatients regarding patients' rights and obligations in Denpasar City. It employed a descriptive observational design with a cross-sectional approach. Data were collected through questionnaires distributed to 200 doctors and 200 inpatients in Denpasar City. The study findings indicated that most doctors had a very good level of knowledge regarding patients' rights (88,5%) and obligations (77,5%). Meanwhile, patients' knowledge of their rights was categorized as very good (55%) and good (37,5%), whereas their knowledge of their obligations was also classified as very good (53,5%) and good (40%). The level of knowledge of doctors and inpatients in Denpasar City regarding patients' rights and obligations fell within the good to very good category. Keywords : Doctor-patient relationship, healthcare quality, knowledge assessment.